1997
DOI: 10.1074/jbc.272.29.18071
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Degradation by Matrix Metalloproteinases

Abstract: Insoluble elastin was used as a substrate to characterize the peptide bond specificities of human (HME) and mouse macrophage elastase (MME) and to compare these enzymes with other mammalian metalloproteinases and serine elastases. New amino termini detected by protein sequence analysis in insoluble elastin following proteolytic digestion reveal the P 1 residues in the carboxyl-terminal direction from the scissile bond. The relative proportion of each amino acid in this position reflects the proteolytic prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(79 citation statements)
references
References 30 publications
1
71
2
Order By: Relevance
“…Elastin is readily degraded by the serine proteases pancreatic and neutrophil (or leukocyte) elastase, as well as several matrix metalloproteinases including MMP-2, MMP-7 (matrilysin), MMP-9 and MMP-12 (metalloelastase) [24,29,39]. In the disc, only limited descriptions of the presence and function of these enzymes currently exist.…”
Section: Roles Of Elastic Fibres In the Ageing And Degeneration Of Thmentioning
confidence: 99%
“…Elastin is readily degraded by the serine proteases pancreatic and neutrophil (or leukocyte) elastase, as well as several matrix metalloproteinases including MMP-2, MMP-7 (matrilysin), MMP-9 and MMP-12 (metalloelastase) [24,29,39]. In the disc, only limited descriptions of the presence and function of these enzymes currently exist.…”
Section: Roles Of Elastic Fibres In the Ageing And Degeneration Of Thmentioning
confidence: 99%
“…[14,24]-Hot alkali extraction results in a protein product that has an amino acid composition that best matches the expected values for elastin. However, due to the harsh conditions, hot alkali-purified elastin shows evidence of degradation [22,25], which must be taken into account when designing experiments with the purified product. It is important to note that incubation at high temperature for longer than 50 minutes will result in extensive peptide bond cleavage.…”
Section: Purification Of Insoluble Elastinmentioning
confidence: 99%
“…The second class was thought to be located in the alanine-rich hydrophobic cross-linked areas of elastin and to lead to catalysis (Heather et al, 1999). Based on the studies reported, the logistic kinetics model was generally adopted to describe the proteolysis process, especially for macromolecular substrates (Mecham et al, 1997). Fig.5 and Table 4 show the experimental results of the kinetics model analysis, respectively.…”
Section: Study On the Kinetics Model Of Elastolysismentioning
confidence: 99%
“…These proteinases require Zn atoms for activity and in contrast to the serine proteinases cleave peptide bonds on the amino-terminal side of the amino acid that determines specificity. Elastase from Bacillus thermoproteolyticus and Streptomyces fradiae are four and eight times more active than PPE (pig pancreatic elastase), respectively, making them some of the most potent elastolytic proteinases reported (Mecham et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation